California's Governor message - Alexander H. Pope:::::: (1959)
A letter from Alexander Pope, Governor Pat Brown's Legislative Secretary, that answers a question that Jane Tolmach's committee asked the Govenor's office. The letter also says that the Govenor would come speak to the Ventura County Democratic Central Committee in Ventura in the future.